The woman who died a lot now with 50% added subplot - Fforde, Jasper 1961- (Penguin Books, 2013)
The Bookworld's leading enforcement officer, Thursday Next, has been forced into semi-retirement following an assassination attempt. After returning home to Swindon and her family to recuperate, she finds that her children have problems that need her attention
First published in the United States by Viking Penguin, 2012
Keywords: Next, Thursday (Fictitious character) / Fiction; Women detectives / England / Fiction; Literary historians / England / Fiction; Characters and characteristics in literature / Fiction; Books and reading / Fiction